Vertex occlusal radiography in localizing unerupted mesiodentes - P Chalakkal; A M Thomas; F Akkara; Ida de Noronha de Ataide (Wolters Kluwer Medknow Publications, 2011)
The aim was to compare the vertex occlusal projection with the anterior maxillary occlusal projection in localizing the position of mesiodentes. Mesiodentes were observed in an 8-year-old boy with an anterior maxillary occlusal radiograph. A vertex occlusal radiograph was taken to compare it with the former in terms of mesiodentes localization with respect to the maxillary central incisors. The vertex occlusal radiograph provided greater details of the position and proximity of mesiodentes with respect to the long axis of maxillary central incisors in comparison to the anterior maxillary occlusal radiograph. Vertex occlusal radiography is an important diagnostic tool in diagnosing the presence, position, and proximity of mesiodentes with respect to the long axis of normally aligned maxillary central incisors. However, it is not recommended for routine use in a patient as its radiation dose is higher than conventional intraoral radiographic methods.